Why choose women's work if it pays less? A structural model of occupational choice - M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2002)
This paper controls for the selection bias associated with occupational choice and the labor force participation decision in estimating the wage penalty for working in female-dominated occupations. Using data from the May 1979 and the April 1993 supplements to the Current Population Survey, the author finds that women working in female-dominated occupations have similar or higher expected wages in their chosen occupation compared to nonfemale-dominated occupations. This result indicates that there is efficient matching between occupations and skills for women in the labor force and refutes the theories of occupational segregation or crowding as determinants of the gender wage differential.
Keywords: 330; Employment (Economic theory); Wages; Labor supply